Relative efficacy of some insecticides for the control of tea mos quito bug, Helopeltis theivora (Waterhouse) in Bangladesh (The Journal of Plant Protection Sciences, 2023)
Tea mosquito bug, Helopeltis theivora Water house (Hemiptera: Miridae) is one of the most  serious pests of tea in Bangladesh. It is also  widely distributed in India, Sri Lanka, Viet nam, Indonesia, Malaysia and Africa. It is  also a phytophagous pest of coffee, cocoa,  cashew etc. A group of genomes are treated as  a mosquito bug. This bug bears no relation to  mosquito and the name ‘Tea Mosquito Bug’  is simply a misnomer. It is considered as one  of the major pests of Bangladesh tea because  it attacks only to the young shoots that are the  actual crop of tea. Ahmed (2) reported that 10 -15% of tea crop is lost annually by Helopeltis which sometimes may go up to 100% crop  loss. Both the nymphs and adults damage the  plant by sucking sap from young leaves, buds  and tender stems. Due to intensive feeding by  nymphs and adults, leaves curl up and are  badly deformed. In addition to direct crop  loss, damage by Helopeltis leads to debilita tion of bushes resulting in die-back with  crows-feet and delayed or meager flushing  thereafter consequently almost the entire crop  is lost. Mamun (6) described that many differ ent tactics are used in IPM strategy for tea  mosquito bug in tea plantation, including cul tural practices, biological control agents, pest resistant varieties, physical barriers and  chemical pesticides etc. Yet chemical insecti cides have remained as the most powerful  tools for controlling this pest in Bangladesh.  From the above point of view, efforts were  made to evaluate the relative efficacy and eco nomic analysis of some insecticides to find  out suitable substitute for efficient control of  tea mosquito bug in Bangladesh tea.
Keywords: Quinalphos+Cypermethrin; pesticides